2015
DOI: 10.1017/s175173111400264x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of CLA and dietary concentrate proportion on blood metabolite concentration and proliferation of peripheral blood mononuclear cells of periparturient dairy cows

Abstract: The study aimed to examine effects of supplemented CLA to periparturient dairy cows receiving different concentrate proportions antepartum (a.p.) to investigate CLA effects on metabolism and immune function. Compared with adapted feeding, highconcentrate diet a.p. should induce a ketogenic metabolic situation postpartum (p.p.) to better understand how CLA works. A total of 64 pregnant German Holstein cows had ad libitum access to partial mixed rations based on concentrate and roughage 3 weeks before calving un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…Neither the CLA nor the EFA+CLA treatment had immediate effects on parameters related to the systemic or hepatic immune response in the cows. Our findings support the results of previous studies demonstrating the failure of CLA treatment to show effects on inflammatory cytokines in dairy cows (Saremi et al, 2012a;Petzold et al, 2015) or bovine peripheral blood mononuclear cells (Renner et al, 2013). The n-3 FA or CLA treatment may influence the inflammatory status and immune response in dairy cows only after an immune challenge (Gandra et al, 2016;Gross et al, 2018).…”
Section: Effects Of Fa Supplementation On Systemic and Hepatic Inflammatory And Antioxidative Statussupporting
confidence: 92%
“…Neither the CLA nor the EFA+CLA treatment had immediate effects on parameters related to the systemic or hepatic immune response in the cows. Our findings support the results of previous studies demonstrating the failure of CLA treatment to show effects on inflammatory cytokines in dairy cows (Saremi et al, 2012a;Petzold et al, 2015) or bovine peripheral blood mononuclear cells (Renner et al, 2013). The n-3 FA or CLA treatment may influence the inflammatory status and immune response in dairy cows only after an immune challenge (Gandra et al, 2016;Gross et al, 2018).…”
Section: Effects Of Fa Supplementation On Systemic and Hepatic Inflammatory And Antioxidative Statussupporting
confidence: 92%
“…(Gerspach et al, 2016;Rehage et al, 1996;Reid & Collins, 1980), but may not necessarily be pathological. In this respect, Petzold et al (2015) refer to a likely enhanced capability…”
Section: Discussionmentioning
confidence: 99%
“…The partial biohydrogenation of linoleic acid produces trans-11 C18:1 FA and cis-9,trans-11 C18:2 CLA (Jenkins et al, 2008). However, recent in vivo or ex vivo studies have demonstrated that CLA has a minor effect on immune response of cows (Petzold et al, 2015;Eger et al, 2017).…”
Section: Introductionmentioning
confidence: 99%